2022
DOI: 10.3390/nano12224073
|View full text |Cite
|
Sign up to set email alerts
|

Improved Activity of Herbal Medicines through Nanotechnology

Abstract: Phytochemicals or secondary metabolites are substances produced by plants that have been shown to have many biological activities, providing a scientific basis for using herbs in traditional medicine. In addition, the use of herbs is considered to be safe and more economical compared to synthetic medicine. However, herbal medicines have disadvantages, such as having low solubility, stability, and bioavailability. Some of them can undergo physical and chemical degradation, which reduces their pharmacological ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 104 publications
0
25
0
Order By: Relevance
“…Numerous studies have shown that various nanoformulations made from naturally occurring polyphenols, including curcumin, quercetin, and resveratrol, dramatically improve the health of individuals with neurological diseases. Medicinal herbs can be encapsulated or loaded in nanostructures, including nanoemulsions, SLNs, liposomes, and NLCs (Dewi et al, 2022). Bioavailability is the principal limitation influencing the translational perspectives of these herbs, with the BBB being the primary obstruction.…”
Section: Nanocarrier Technology-based Delivery Systems For the Treatm...mentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous studies have shown that various nanoformulations made from naturally occurring polyphenols, including curcumin, quercetin, and resveratrol, dramatically improve the health of individuals with neurological diseases. Medicinal herbs can be encapsulated or loaded in nanostructures, including nanoemulsions, SLNs, liposomes, and NLCs (Dewi et al, 2022). Bioavailability is the principal limitation influencing the translational perspectives of these herbs, with the BBB being the primary obstruction.…”
Section: Nanocarrier Technology-based Delivery Systems For the Treatm...mentioning
confidence: 99%
“…Liquid lipid is the core component of the NLCs, according to the literature finding Vitamin E to be the most suitable for our purpose, as it exhibits some exclusive properties, including its highly efficient antioxidant property, which delays the neuronal damage caused by OS. It also enhances the immunomodulatory effects of NCs by increasing the chemical stability of entrapped drugs (Dewi et al, 2022). Since vitamin E dissolves in lipids, it can be detected in LDL.…”
Section: Theoretical Modified Proposed Formulation Of Engeletin Again...mentioning
confidence: 99%
See 1 more Smart Citation
“…Nanotechnology-driven herbal medicines offer potential and special qualities, such as turning less soluble and poorly absorbed ingredients, and incorporating unstable ingredients into promising pharmaceuticals. As a result, nanotechnology-based delivery methods offer a great opportunity to improve herbal activity and resolve problems using herbal therapy [ 8 ] ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…The literature has stated that nanostructured systems based on nanotechnology can improve the characteristics of plant extracts. This might enhance several extract features, such as plant extract action, increase the sustained release of active ingredients, lower the needed dose, lessen side effects, and improve activity [15].…”
Section: Introductionmentioning
confidence: 99%